A Clinical Decision Analysis for Use of Antibiotic Prophylaxis for Nonabsorbable Nasal Packing. (November 2021) - Maul, Ximena; Dincer, Berkay C.; Wu, Arthur W.; Thamboo, Andrew V.; Higgins, Thomas S.; Scangas, George A.; Oliveira, Kristin; Ho, Allen S.; Mallen-St Clair, Jon; Walgama, Evan
Objective: Nonabsorbable nasal packing is often placed for the treatment of epistaxis or after sinonasal or skull base surgery. Antibiotics are often prescribed to prevent toxic shock syndrome (TSS), a rare, potentially fatal occurrence. However, the risk of TSS must be balanced against the major risk of antibiotic use, specifically Clostridium difficile colitis (CDC). The purpose of this study is to evaluate in terms of cost-effectiveness whether antibiotics should be prescribed when nasal packing is placed. Study Design: A clinical decision analysis was performed using a Markov model to evaluate whether antibiotics should be given. Setting: Patients with nonabsorbable nasal packing placed. Methods: Utility scores, probabilities, and costs were obtained from the literature. We assess the cost-effectiveness of antibiotic use when the risk of community-acquired CDC is balanced against the risk of TSS from nasal packing. Sensitivity analysis was performed for assumptions used in the model. Results: The incremental cost-effectiveness ratio for antibiotic use was 334, 493 US dollars (USD)/quality-adjusted life year (QALY). Probabilistic sensitivity analysis showed that not prescribing antibiotics was cost-effective in 98.0% of iterations at a willingness to pay of 50, 000 USD/QALY. Sensitivity analysis showed that when the risk of CDC from antibiotics was greater than 910/100, 000 or when the incidence of TSS after nasal packing was less than 49/100, 000 cases, the decision to withhold antibiotics was cost-effective. Conclusions: Routine antibiotic prophylaxis in the setting of nasal packing is not cost-effective and should be reconsidered. Even if antibiotics are assumed to prevent TSS, the risk of complications from antibiotic use is of greater consequence. Level of Evidence: 3a